PENGARUH KOMUNIKASI TERHADAP MOTIVASI KERJA PADA CV. PERSAUDARAAN OKE SEKALI - Siti Nurjanna Ayu Lestari; Agung Widhi Kurniawan, Muhammad Ilham Wardhana Haeruddin, Burhanuddin, Uhud Darmawan Natsir (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to determine whether there is an effect of communication on work motivation at Cv. Brotherhood Okay Once. The independent variable in this study is Communication while the dependent variable is Work Motivation. The population in this study are employees who work at Cv. Brotherhood Okay Once. While the sample used is as many as 30 people. The sampling technique in this study is a saturated sample. Data collection was carried out using a questionnaire. The data analysis technique used is multiple linear regression analysis using SPSS 23 for windows. Overall the results of this study indicate that the Communication variable has a significant influence on the Work Motivation variable of CV employees. Brotherhood Okay Once. This is proven by obtaining the correlation value. Which means if Communication is assumed to be zero, Work Motivation on CV. The Brotherhood is Okay Once it doesn't change, but if Communication has increased, then this can affect Work Motivation on the CV. Brotherhood Okay Once